2007
DOI: 10.1111/j.1365-313x.2007.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional paternal inheritance of plastids in Arabidopsis suggests that low‐frequency leakage of plastids via pollen may be universal in plants

Abstract: SummaryPlastid DNA is absent in pollen or sperm cells of Arabidopsis thaliana. Accordingly, plastids and mitochondria, in a standard genetic cross, are transmitted to the seed progeny by the maternal parent only. Our objective was to test whether paternal plastids are transmitted by pollen as an exception. The maternal parent in our cross was a nuclear male sterile (ms1-1/ms1-1), spectinomycin-sensitive Ler plant. It was fertilized with pollen of a male fertile RLD-Spc1 plant carrying a plastid-encoded spectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 31 publications
1
57
1
Order By: Relevance
“…In Arabidopsis, no plastids are found in sperm cells (Tang et al, 2009;Wang et al, 2010), and DPD1 is unlikely to affect maternal ptDNA inheritance. Therefore, plastid maternal inheritance is determined primarily by the exclusion of plastids in germ cells rather than ptDNA amounts in Arabidopsis (Martínez et al, 1997;Azhagiri and Maliga, 2007). In fact, our F1 analysis between Cvi and dpd1 showed that DPD1 did not affect plastid inheritance (see Supplemental Figure 6 online).…”
Section: Maternal Inheritance and Possible Role Of Organelle Dna Degrmentioning
confidence: 76%
“…In Arabidopsis, no plastids are found in sperm cells (Tang et al, 2009;Wang et al, 2010), and DPD1 is unlikely to affect maternal ptDNA inheritance. Therefore, plastid maternal inheritance is determined primarily by the exclusion of plastids in germ cells rather than ptDNA amounts in Arabidopsis (Martínez et al, 1997;Azhagiri and Maliga, 2007). In fact, our F1 analysis between Cvi and dpd1 showed that DPD1 did not affect plastid inheritance (see Supplemental Figure 6 online).…”
Section: Maternal Inheritance and Possible Role Of Organelle Dna Degrmentioning
confidence: 76%
“…Examples include the monocot species Setaria italica and the dicots tobacco (Avni and Edelman, 1991;Ruf et al, 2007;Svab and Maliga, 2007), petunia (Petunia hybrida;Derepas and Dulieu, 1992), and Arabidopsis (Arabidopsis thaliana; Azhagiri and Maliga, 2007). Another mechanism that could yield new combinations of plastids and CMS mitochondria is the horizontal gene transfer of mitochondrial DNA, an evolutionary mechanism described in multiple species (Richardson and Palmer, 2007;Bock, 2010).…”
Section: Single Origin Of Cms-t Cytoplasm In Maizementioning
confidence: 99%
“…For example, the use of plastome mutants by Correns and Baur formed the foundation of cytoplasmic genetics (Baur, 1909;Correns, 1909;Baur, 1910;Hagemann, 2010). Plastome mutants continue to play an important role in elucidating the rules of nonMendelian inheritance (Chiu and Sears, 1985;Azhagiri and Maliga, 2007;Ruf et al, 2007) and in studying chloroplast gene expression and photosynthesis (Schaffner et al, 1995;Landau et al, 2009). Moreover, plastid mutants provide selectable markers for antibiotic or herbicide resistance that are widely used in molecular biology, biotechnology, and agriculture (Schmitz-Linneweber et al, 2005;Powles and Yu, 2010).…”
Section: Introductionmentioning
confidence: 99%